CAÑAR DESTANINDA GELENEK VE GEÇİŞ TÖRENLERİ BAĞLAMINDA SOSYAL HAYAT - Zehra Görkem Duran Gültekin (Motif Akademi Halkbilimi Dergisi, 2020)
Epics are the identities of the nations. It is possible to find the data of religious, political, social and cultural values of a society in epics. The epics of Siberian Turks are very rich in this respect, like the epics of the entire Turkish World. Therefore, the traces of the oldest Turkish culture can be followed in these epics. Altai Turks still keep alive the elements of ancient Turkish religion and shamanism. The epic Cañar, the most voluminous epic of Altai Turks in the literature, draws attention with its rich elements. So much so that this three-volume 36050 verse text has an important place not only in the Altai Turks but also in the epic tradition of the whole Turkish world. The plot of the epic is shaped around the tough struggle of the central hero Cañar and his sister Cañarçı against Erlik-biy. The motifs that appeared in this struggle provide important data on the religious, cultural and social life of the Altai Turks at that time. In this context, we will focus on the social life in the Cañar Epic in the context of birth, naming, marriage, deat/mourning rituals.